THE COMPARASION OF THE EFFECTIVENESS OF THE IMPLEMENTATION OF GIVING TASK ON PROBLEM OF COOPERATIVE SETTING OF STAD TYPE AND COOPERATIVE SETTING OF NHT TYPE IN TRIGONOMETRY TO CLASS X STUDENT AT MA DDI ALLIRITENGAE IN MAROS - Siti Aisyah (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
The problems of the research were: (1) whether the implementation of giving task on problem of cooperative setting of STAD type was effective to implement in trigonometry to class X student at MA DDI Alliritengae in Maros District,(2) whether the implementation of giving task on problem of cooperative setting of NHT type was effective to implement in trigonometry to class X student at MA DDI Alliritengae in Maros District,(3) whether the implementation of giving task  problem of cooperative setting of NHT type was effective to implement than cooperative setting of STAD type in trigonometry to class X student at MA DDI Alliritengae in Maros District. The popualations of the research were all the student in class X  at MA DDI Alliritengae in Maros District and the samples were class X1 as the exsperiment class I and class X2 as the exsperiment class II, chosen by using random sampling. The data which was collected consisted of learning result, students’ activity, and students’ response toward learning. The data was analyzed by using inferential and descriptive  analysis. The results of the research showed that: (1) descriptively, the students’ learning results in  mathematics in exsperiment class I was in high category, the average gain was normalized in medium category, the students’ activity was in good category and the students’ response toward the learning was positive. Inferentially the students’ learning result in mathematics was more than 74.9, the average gain was normalized more than 0.29. Generally, it could be concluded that giving task on problem of cooperative setting of STAD type was effective to be implemented in class at MA DDI Alliritengae in Maros District, (2) descriptively, the students’ learning results in  mathematics in exsperiment class II was in high category, the average gain was normalized in high category, the students’ activity was in very good category and the students’ response toward the learning was very positive. Inferentially the students’ learning result in mathematics was more than 74.9, the average gain was normalized more than 0.29. Generally, it could be concluded that giving task on problem of cooperative setting of NHT type was effective to be implemented in class at MA DDI Alliritengae in Maros District, (3) the result of hypothesis test in significant level α = 0.05, with t-test showed that giving task on problem of cooperative setting of NHT type was more effective than giving task on problem of cooperative setting of NHT type  in class X at  MA DDI Alliritengae in Maros District